Pelatihan Pembuatan Bakso Daging Ayam Afkir dengan Penambahan Antioksidan Alami pada Ibu Rumah Tangga di Kelurahan Padaidi, Kabupaten Pinrang - Hajrawati Hajrawati; Muhammad Irfan Said; Fatma Maruddin; Farida Nur Yuliati; Wardhani Hakim; Hamsah Hamsah; Nurul Mutiah Rasak (To Maega : Jurnal Pengabdian Masyarakat, 2024)
housewives in the Padaidi village, Mattiro Bulu sub-district, Pinrang regency are not economically productive; they rely solely on their husbands' income. On the other hand, this area is predominantly inhabited by chicken egg farmers. Generally, laying hens are culled after 70-76 weeks and have tougher meat compared to broiler chickens, resulting in very low market value. Therefore, technological intervention is needed to increase the added value of culled chickens. One of the alternatives to address this issue is empowering housewives to develop productive businesses in the field of processing livestock products, particularly processed culled chicken meat products such as meatballs, nuggets, sausages, and other processed meat products with the addition of natural antioxidants to produce healthier and more nutritious functional food products. The implementation method included coordination, discussions, education, training, and mentoring for partners (housewives). Based on the results, participants were very enthusiastic about attending training on making meatball from culled chicken meat with the addition of moringa leaf powder as a natural antioxidant. This training activity was expected to stimulate and motivate the local community, especially housewives, to engage in productive businesses in processing livestock products to help improve nutrition and family income.